Father Involvement in the First Year After Prison: Considerations for Social Work. (November 2021) - Charles, Pajarita; Frankham, Emma; Garthe, Rachel C.; Visher, Christy A.; Kay, Anna L.
Purpose: Paternal incarceration poses significant concerns for fathers and their children. Despite the known negative consequences, little is understood about father involvement after prison. This study aims to further understanding of fatherhood following incarceration to inform future intervention strategies. Method: Using data from the Urban Institute's Returning Home: Understanding the Challenges of Prisoner Reentry Study ( N = 326), we conduct bivariate and multivariate analyses to examine three dimensions of father involvement and predictors of involvement at two time points after prison. Results: Findings reveal generally high levels of father involvement in the first year following incarceration. Father-child contact during prison and increased work hours after prison showed positive effects on early father involvement, while post-prison engagement and contact following release were associated with later involvement. Conclusions: Promoting father-child contact and positive relationships during incarceration may be important for future father involvement after release. Potential social work and criminal justice practice and research opportunities are discussed.